1993
DOI: 10.1212/wnl.43.4.751
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of amyotrophic lateral sclerosis and the use of natural history controls in therapeutic trials

Abstract: We analyzed the natural history of amyotrophic lateral sclerosis in 277 patients. Our goal was to develop a better understanding of the clinical disease and thus improve the design of therapeutic trials. The Tufts Quantitative Neuromuscular Exam (TQNE) was used as the primary assessment instrument. Our analysis suggested that although more observations are desirable, six monthly TQNEs were adequate to establish the rate of disease progression. We observed a spectrum of deterioration rates without definable sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 0 publications
4
26
0
Order By: Relevance
“…Moreover, given the well-known correlation between disease progression and survival, [12][13][14]34 we expected to find that age at onset, time between first symptom and first examination, and site of symptom onset, well established predictors of survival in ALS, also act as significant and independent covariates of disease progression, although such findings remain at odds with some previous reports. 22,23,28,30 We also found that initial FVC was significantly associated with disease progression, even after adjustment for age, gender, and site of onset. Moreover, in our previous study, this association between FVC and disease progression remained significant even after additional correction for FS-FE time and riluzole use.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Moreover, given the well-known correlation between disease progression and survival, [12][13][14]34 we expected to find that age at onset, time between first symptom and first examination, and site of symptom onset, well established predictors of survival in ALS, also act as significant and independent covariates of disease progression, although such findings remain at odds with some previous reports. 22,23,28,30 We also found that initial FVC was significantly associated with disease progression, even after adjustment for age, gender, and site of onset. Moreover, in our previous study, this association between FVC and disease progression remained significant even after additional correction for FS-FE time and riluzole use.…”
Section: Discussionsupporting
confidence: 52%
“…Based on our present data, as well as on our previous reports, 10 we suggest that patients be assigned to treatment groups by stage of disease (AALS total score at the time of first examination) and initial rate of clinical decline. However, we 13,35,36 and others 19,28 have previously suggested that the correlation between predicted and actual rate of clinical decline is stronger if more data points are available for every patient. By contrast, both the preslope-based and FE-based predictions of the subsequent rate of disease progression require only one measurement be performed at the initial examination.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Although data are conflicting [2,3], many authorities consider that ALS follows a linear course [4][5][6] and research indicates that functional status might predict survival [7], but the true shape of the progression curve as well as the best means to identify patients with similar survival rates are not known; some of the most severely disabled patients are among the longest survivors. Defining the shape of the progression curve and phenotypes with distinct survival patterns has implications for clinical care and study design.…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of neurodegeneration in ALS has been described as overall linear, albeit with some variations [228,229]. One of the biggest discrepancies between individuals is the evolution of the disease, which ranges from death in less than 6 months to a limited handicap after more than 10 years following the initial diagnosis.…”
Section: Clinical Aspectsmentioning
confidence: 99%